2017
DOI: 10.3390/cli5020028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Climatic and Non-Climatic Factors on Cassava Yields in Togo: Agricultural Policy Implications

Abstract: This paper examines the effects of climatic and non-climatic factors on cassava yields in Togo using an Autoregressive Distributed Lag (ARDL) modelling approach and pairwise Granger Causality tests. Secondary data on production statistics, rural population, climate variables, prices and nominal exchange rate for the period 1978-2009 are used. Results for estimated short-and long-run models indicate that cassava yield is affected by both 'normal' climate variables and within-season rainfall variability. An inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Nigerian farmers also bear the mentality that fertilizer application to cassava farm is unnecessary and wasteful 2 . From our regression modeling, the relevance of other environmental variables that influence cassava yield in Nigeria was confirmed, i.e., aside from the climate, soil conditions are key to cassava yield 31,58 . Our field investigations showed that farmers are still cultivating the local varieties of cassava even in South-western Nigeria where IITA is located.…”
Section: Geospatial Relationship Between Cassava Yield and Environmenmentioning
confidence: 60%
“…Nigerian farmers also bear the mentality that fertilizer application to cassava farm is unnecessary and wasteful 2 . From our regression modeling, the relevance of other environmental variables that influence cassava yield in Nigeria was confirmed, i.e., aside from the climate, soil conditions are key to cassava yield 31,58 . Our field investigations showed that farmers are still cultivating the local varieties of cassava even in South-western Nigeria where IITA is located.…”
Section: Geospatial Relationship Between Cassava Yield and Environmenmentioning
confidence: 60%
“…Due to the impact of ACMD and CBSD (Boansi, 2017;Hillocks et al, 2002b), finding sufficient disease-free planting material was difficult at the study onset. Cassava transplant cuttings should be robust (Polthanee and Wongpichet, 2017) including only the middle brownskinned portions of the stem and approximately 20 to 25 cm long with 5 to 8 nodes (James et al, 2000).…”
Section: Factors Affecting Yield Responsementioning
confidence: 99%
“…Cassava provides edible leaves and tubers (Boansi, 2017;Li et al, 2010) and is produced almost *Corresponding author. E-mail: ibcuvaca@ksu.edu.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations